2021
DOI: 10.56499/jppres21.1081_9.6.878
|View full text |Cite
|
Sign up to set email alerts
|

The real impact of COVID-19 on community pharmacy professionals as part of the primary health care frontier workforce in Spain

Abstract: Context: Spain was at the epicenter of the pandemic. Health centers across Spanish territory were not able to respond to non-emergency enquiries, leaving community pharmacies as the first point of patient’s contact. Aims: To investigate the impact of COVID-19 on the mental and physical health of community pharmacy teams across Spain. Methods: A cross-sectional observational study was performed with community pharmacy professionals throughout Spain. A questionnaire designed by our collaborator from the United… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
(13 reference statements)
0
6
0
1
Order By: Relevance
“…The shortage of safety equipment, antiseptics, disinfectants, dietetic products, supplements, and medicines were reported in most of the selected studies. 10 , 17. , 18.…”
Section: Main Strategies For Addressing Covid-19mentioning
confidence: 99%
See 3 more Smart Citations
“…The shortage of safety equipment, antiseptics, disinfectants, dietetic products, supplements, and medicines were reported in most of the selected studies. 10 , 17. , 18.…”
Section: Main Strategies For Addressing Covid-19mentioning
confidence: 99%
“…Despite the above findings, many authors also identified concerns regarding the fear and misinformation of professionals about the health outcomes in the face of the virus, lack of training or lack of time for health education of patients and search for updates on the world scene, in addition to the efforts to identify and combat false news. 17 , 20 , 22 , 23 , 26 , 32 , 39 , 43 Nevertheless, high basic knowledge on the questions related to transmission, drugs, preventive measures, testing, and duration of quarantine was established, indicating that most of the study samples had knowledge about the general information on COVID-19. 10 , 17.…”
Section: Main Strategies For Addressing Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…28,31) (의약품 조제를 제 외하면) 대면으로 이루어지던 서비스가 줄어들거나 중단되었 으며, 28,32) 연구에 참여한 약국종사자들은 이러한 상호작용의 축소로 발생하는 코로나19 또는 의약품 관련 오정보에 대해 우려를 나타내었다. 27,28,31,[35][36][37]39,45) 상담시간 및 상담 내용의 포괄성을 평가한 한 연구는 약사가 유용한 정보제공자임을 보고하였다. an increase in customer traffic to their pharmacy 81% an increase in being asking relevant questions with flu-like symptoms before signposting them to the appropriate care 75% willing to offer their assistance for mass testing of Covid-19 53%…”
Section: 연구 결과unclassified